Taxpayer Compliance in SMEs Sector: A Theory of Planned Behavior - Made Sudiartana; Ni Putu Yuria Mendra (Jurnal Keuangan dan Perbankan, 2018)
The low level of taxpayer compliance is assessed as one of the causes of not achieving the target of tax revenue in Indonesia. One of the efforts made by the government to optimize tax revenue is by requiring UMKM sector to fulfill the obligation of taxation. Based on the above, the researcher is interested to conduct research on taxpayer compliance of UMKM using the psychological approach that is Theory of Planned Behavior. This theory describes the effect of attitudes on behavior, subjective norms, and perceived behavioral control on taxpayer compliance intent and behavior. This research uses a survey method at formal UMKM in Bali Province. Methods of sampling using proportional random sampling. Data analysis using the Structural Equation Model (SEM). The results showed that attitudes toward behavior, subjective norms, and perceived behavioral control have an effect on one's intentions to comply with tax provisions. Nevertheless, perceived behavioral control variables have no direct effect on individual tax compliance behavior. The test results on the variable intention to comply with tax compliance behavior support Theory of PlannedJEL Classification: H24; H26; M41DOI: https://doi.org/10.26905/jkdp.v22i2.1561